Modeling and design study of energy generation through high-speed wind at the spillways of hydroelectric power station. Issue 3 (June 2021) - Malik, Muhammad Suleman; Khan, Muhammad Omer; Aamir, Syed Muhammad
The customary energy assets are progressively draining, and the quest for using sustainable power source for power generation is picking up ubiquity for a safe energy demand. Energy recovery thought is introduced to use the pressurized wind caused because of water flow from the spillway of the hydel generating station. The fast wind is caused because of water flow from the supply at higher head to catchment zone at lower head. By appropriate demonstrating the structure parameters of the wind turbines, this fast wind can be used to create power by introducing it in reasonable areas. The consequences of two contextual investigations have been analyzed, and the capability of wind power in those areas has been evaluated. The produced wind power is taken back to the main system and can either be used for charging the batteries or can be used for auxiliary equipment.